Targeting Fluorescent Sensors to Endoplasmic Reticulum Membranes Enables Detection of Peroxynitrite During Cellular Phagocytosis - Knewtson, Kelsey E. (ACS Chem Biol, 2018)
Peroxynitrite is a highly reactive oxidant derived from superoxide and nitric oxide. In normal vertebrate physiology, some phagocytes deploy this oxidant as a cytotoxin against foreign pathogens. To provide a new approach for detection of endogenous cellular peroxynitrite, we synthesized fluorescent sensors targeted to membranes of the endoplasmic reticulum (ER). The very high surface area of these membranes, approximately 30 times greater than the cellular plasma membrane, was envisioned as a vast intracellular platform for the display of sensors to transient reactive species. By linking an ER-targeted profluorophore to reactive phenols, sensors were designed to be cleaved by peroxynitrite and release a highly fluorescent ER-associated rhodol. Studies of kinetics in aqueous buffer revealed a linear free energy relationship where electron-donating substituents accelerate this reaction. However, in living cells, the efficiency of detection of endogenous cellular peroxynitrite was directly proportional to association with ER membranes. By incorporating a 2,6-dimethylphenol to accelerate the reaction and enhance this subcellular targeting, endogenous peroxynitrite in living RAW 264.7 macrophage cells could be readily detected after addition of antibody-opsonized tentagel microspheres, without additional stimulation, a process undetectable with other known fluorescent sensors. This approach provides uniquely sensitive tools for studies of transient reactive species in living mammalian cells.